Advances in miRNA-Mediated Mucin Regulation - Krishn, Shiv Ram (Curr Pharmacol Rep, 2015)
MicroRNAs (miRNAs) are an important class of small non-coding RNAs that direct post-transcriptional gene regulation by different mechanisms. Mounting evidences from numerous studies in the last decade have unraveled that deregulated miRNAs, and their cognate target expressions are strongly implicated in the carcinogenesis. Recent advances have highlighted miRNA-mediated regulation of mucins that have critical role in inflammation and cancer biology. The aberrant expression and differential glycosylation of mucins cause tumorigenesis, metastasis, chemoresistance and poor outcome of cancer patients, thus recognizing them as attractive therapeutic targets. Though current mucin-based therapies (antibodies, vaccines, immunotherapy, peptide inhibitors) have shown preclinical utility but only a handful promise for clinical transferability. In this context, understanding miRNA-mediated modulation of multiple mucin(s) expression and function gives a new hope for future anti-tumor therapeutics. Herein, we reviewed miRNA biogenesis, mechanism of action, and their role in tumor development. Further, we provide an overview of miRNA-mediated mucin regulation and their application as anticancer therapeutics.